2009
DOI: 10.1002/mrm.21888
|View full text |Cite
|
Sign up to set email alerts
|

Radial sliding‐window magnetic resonance angiography (MRA) with highly‐constrained projection reconstruction (HYPR)

Abstract: Sufficient temporal resolution is required to image the dynamics of blood flow, which may be critical for accurate diagnosis and treatment of various intracranial vascular diseases, such as arteriovenous malformations (AVMs) and aneurysms. Highlyconstrained projection reconstruction (HYPR) has recently become a technique of interest for high-speed contrast-enhanced magnetic resonance angiography (CE-MRA). HYPR provides high frame rates by preferential weighting of radial projections while maintaining signal-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…This is usually traded off with reduced SNR. These and other effects have been studied in detail previously .…”
Section: Mri Of Time‐varying Signalsmentioning
confidence: 85%
See 1 more Smart Citation
“…This is usually traded off with reduced SNR. These and other effects have been studied in detail previously .…”
Section: Mri Of Time‐varying Signalsmentioning
confidence: 85%
“…However, if an image is ascribed to some time T because that is the time at which central k ‐space is measured, then the use of any data measured after that specific time in forming that image will cause artifactual nonzero signal in blood vessels in advance of the contrast material actually arriving there. This is called "anticipation artifact" and has been described in Cartesian as well as non‐Cartesian MRA acquisition. A tell‐tale sign is the premature appearance of slight but nonzero signal in venous structures several frame intervals prior to significant enhancement.…”
Section: Mri Of Time‐varying Signalsmentioning
confidence: 99%
“…(18, 19) HYPRFlow is well suited for characterizing AVMs and DAVFs because whole brain coverage allows the whole lesion to be characterized which is possible because the relative sparsity of vessels in 3D space allows for the use of undersampling techniques such as radial acquisition (VIPR). Previous work has demonstrated that use of the HYPR reconstruction method provides improved SNR compared to radially sampling k -space with a sliding window reconstruction method (33)…”
Section: Discussionmentioning
confidence: 99%
“…30 The advantage of combining radial encoding and constrained reconstructions to increase SNR has been previously demonstrated in healthy subjects 31 and patients with AVMs. 32 …”
Section: Discussionmentioning
confidence: 99%